Potential Application of Algae in Biodegradation of Phenol: A Review and Bibliometric Study - Radziff, Syahirah Batrisyia Mohamed; Ahmad, Siti Aqlima; Shaharuddin, Noor Azmi; Merican, Faradina; Kok, Yih-Yih; Zulkharnain, Azham; Gomez Fuentes, Claudio German; Wong, Chiew-Yen (My University, 2021)
One of the most severe environmental issues affecting the sustainable growth of human society is water pollution. Phenolic compounds are toxic, hazardous and carcinogenic to humans and animals even at low concentrations. Thus, it is compulsory to remove the compounds from polluted wastewater before being discharged into the ecosystem. Biotechnology has been coping with environmental problems using a broad spectrum of microorganisms and biocatalysts to establish innovative techniques for biodegradation. Biological treatment is preferable as it is cost-effective in removing organic pollutants, including phenol. The advantages and the enzymes involved in the metabolic degradation of phenol render the efficiency of microalgae in the degradation process. The focus of this review is to explore the trends in publication (within the year of 2000-2020) through bibliometric analysis and the mechanisms involved in algae phenol degradation. Current studies and publications on the use of algae in bioremediation have been observed to expand due to environmental problems and the versatility of microalgae. VOSviewer and SciMAT software were used in this review to further analyse the links and interaction of the selected keywords. It was noted that publication is advancing, with China, Spain and the United States dominating the studies with total publications of 36, 28 and 22, respectively. Hence, this review will provide an insight into the trends and potential use of algae in degradation.
Keywords: phenol; phenolic compounds; biodegradation; phycoremediation; algae; hazardous pollutant